STRATEGI KOMUNIKASI PENGEMBANGAN SUMBER DAYA MANUSIA PONDOK PESANTREN SALAFI (Studi Kasus tentang Strategi Komunikasi Pengembangan SDM Pondok Pesantren Miftahul Huda Tasikmalaya) - Dhita Prasanti (Jurnal Nomosleca, 2017)
AbstractAn organization certainly has goals and characteristics that differentiate it from other organizations. To achieve these objectives, organizations need well-planned and correct communication strategies. In this study, researchers take a religious social organization, namely Pondok Pesantren Salafi. With religious values ??and salafi system is a boarding school admitted salafi community and has its own characteristics. In this case, researchers raised about Communication Strategy of Human Resource Development Salafi Pesantren Miftahul Huda Tasikmalaya.This study aims to determine the communication strategy conducted by boarding school Miftahul Huda in the development of human resources. The research method used is case study method. In this case, the data collection technique is done by in-depth interview, observation, and documentation study. The theory of communication suitable for use in this research is the theory of symbolic interaction.The results of this study indicate that communication strategy of Miftahul Huda Pondok Pesantren in the development of its human resources include: audience, message source, media, message content, promotion, result, and interruption related to communication management strategy applied in human resource development is command management imama jamaah which in its application use the doctrine of tawhid ideology as philosophy and ta'at and obedient to imam as operational doctrine.Keywords: Communication Strategy, Development, Human Resources, Salafi Pesantren DOI : https://doi.org/10.26905/nomosleca.v3i1.1476